EMPLOYEE READINESS IN FACING CHANGES IN THE BUDGET SYSTEM AT PT SENTANA MUDA WIBAWA - Maryam, Siti; Kholilah, Kholilah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
This study aims to determine the readiness of employees in facing changes in the budget system at PT Sentana Muda Wibawa. The research method used is qualitative research to obtain information about the readiness of employees in the face of changes in the budget system and to reveal the situations and obstacles faced by the company with such changes. Data obtained from interviews with key informants. The data analysis method in this study is to collect data, reduce data, present data, and draw conclusions. The results of this study prove the readiness of PT Sentana Muda Wibawa to face the demands of budget system changes realized into four main components, appropriateness, management support, efficacy of change, and personal value. Employees of PT Sentana Muda Wibawa are very optimistic about-facing changes in the budget system, although there are some obstacles in the implementation process.